The Role of Socio-Philosophical Factors in Strengthening the Historical Memory of Youth - Akhmadjanov Akmaljon Pulatjonovich (Indonesian Journal Publisher, 2025)
The purpose of this research is to examine the role of socio-philosophical factors in strengthening the historical memory and consciousness of youth in the context of globalization. Using a qualitative and analytical method, the study investigates how education, cultural heritage, media, and national ideology influence the formation of patriotic identity and collective memory among young people in Uzbekistan. Through the review of philosophical, sociological, and pedagogical literature, the research highlights that historical consciousness not only connects individuals with their past but also serves as a moral and ideological safeguard against cultural alienation. The findings indicate that fostering historical memory through national education, monument preservation, and civic engagement promotes resilience, national pride, and social cohesion. The study concludes that strengthening the historical memory of youth is essential for sustainable national development and the preservation of cultural identity amid global transformations.